Seguindo a jornada de um celular: etnografia do circuito sacoleiro entre Paraguai e Brasil - Cameran, Gabriel Antonio (2024)
There is a cellphone trade that happens mainly from Ciudad del Este (PY). It will be presented based on two specific journeys: “artisan” and “systematic”. This research is part of a movement that aims to think about different faces of “popular globalization” indicating actors, strategies and accumulation. Analysing the characteristics of these journeys, it is presented that sacolagem is a fundamental part of contemporary globalization, since it creates tension, legitimations, normative regimes and circulation of money displaced from hegemonic elites such as established retail stores. To capture these displacements, we operate multi-situated ethnography, inserting possible journeys, in other words, in episodic sequences of displacement captured in the field, and complemented with videos and documentaries representing the observed reality. Moreover, secondary data such as those from the Internal Brazilian Revenue Service and the National Telecommunications Agency (ANATEL) were collected and processed.